Resveratrol promotes sensitization to Doxorubicin by inhibiting epithelial‐mesenchymal transition and modulating SIRT1/β‐catenin signaling pathway in breast cancer - Xiaoxia Jin; Yingze Wei; Yushan Liu; Xiaoyun Lu; Fei Ding; Jiatai Wang; Shuyun Yang (Cancer Medicine)
Abstract Breast cancer is one of the leading fatal diseases for women worldwide who cannot have surgery typically have to rely on systemic chemotherapy to extend their survival. Doxorubicin (DOX) is one of the most commonly used chemotherapeutic agents against breast cancer, but acquired resistance to DOX can seriously impede the efficacy of chemotherapy, leading to poor prognosis and recurrences of cancer. Resveratrol (RES) is a phytoalexin with pharmacological antitumor properties, but its underlying mechanisms are not clearly understood in the treatment of DOX‐resistant breast cancer. We used cell viability assays, cell scratch tests, and transwell assays combined with Western blotting and immunofluorescent staining to evaluate the effects of RES on chemoresistance and the epithelial‐mesenchymal transitions (EMTs) in adriamycin‐resistant MCF7/ADR breast cancer cells, and to investigate its underlying mechanisms. The results showed that a treatment of RES combining with DOX effectively inhibited cell growth, suppressed cell migration, and promoted cell apoptosis. RES reversed EMT properties of MCF7/ADR cells by modulating the connection between SIRT1 and β‐catenin, which provides a hopeful therapeutic avenue to conquer DOX‐resistance and thereby prolong survival rates in breast cancer patients.